Maqashid al-Shariah and Stunting Prevention: Developing a Muslim Family-Based Child Health Protection Model - Muhammadong Muhammadong (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
Stunting still be a big problem in child health development. Stunting is related to dietary deficits but also influenced by parenting, economic situations, cleanliness, education and religious views of families. This research aims to develop a model of child health protection based on Muslim families with the perspective of maqashid al-shariah as an integrative method to avoid stunting. The research is based on a qualitative methodology with a conceptual-empirical design. Data were collected through a literature review and qualitative in-depth interviews with families, health workers, religious leaders and policymakers and analyzed using thematic analysis. The results showed that the ideas of hifz al-nafs, hifz al-nasl, hifz al-‘aql, hifz al-mal, and hifz al-din can be integrated into family practices to promote stunting prevention. The model proposed centres on the family as a hub of intervention by means of nutritional satisfaction, maternity & child protection, responsive parenting, better health literacy, sanitation, economic resilience & internalization of religious obligation. It also promotes the engagement of fathers, promotes community support and coordination between health services and religious organizations to continue stunting prevention from the preconception period through early infancy. The findings confirmed that Maqashid al-Shariah can be used as an ethical and operational framework in reducing stunting. The research says: National strategies for stunting prevention should integrate health, family, socioeconomic and Islamic value-based approaches in a comprehensive, effective and sustainable manner.